The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Authorea
DOI: 10.22541/au.158274769.98869554
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning improves bleaching susceptibility in the reef-building coral Pocillopora acuta through modulations in autophagy pathway

Abstract: Stony corals heavily rely on their intracellular algal symbionts for energetical supply. Increasing extreme weather driven by climate change often leads to disruption of the symbiosis and to coral death, threatening the sole existence of coral reefs, the key underwater ecosystems. As climate change mitigation outcomes are uncertain, it is important to search for ways to increase coral resilience towards future climate conditions, thermal extremes in particular. It has been shown that corals can withstand stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Transcriptomic studies in acclimatized corals shed light on the main gene families and cellular pathways that play a role in the bleaching process, but functional studies have been largely missing in reef-building corals (32,33,35,49). Recently, we showed that preconditioning in Pocillopora acuta leads to improved thermal tolerance due to modulations in the programmed cell death pathway (PCD), most likely via autophagy/symbiophagy (39). However, the primary signals or molecular consequences of such a prolonged symbiosis maintenance under thermal stress are unclear.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Transcriptomic studies in acclimatized corals shed light on the main gene families and cellular pathways that play a role in the bleaching process, but functional studies have been largely missing in reef-building corals (32,33,35,49). Recently, we showed that preconditioning in Pocillopora acuta leads to improved thermal tolerance due to modulations in the programmed cell death pathway (PCD), most likely via autophagy/symbiophagy (39). However, the primary signals or molecular consequences of such a prolonged symbiosis maintenance under thermal stress are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This difference was more pronounced after 5 days of heat stress. However, PC corals still lost symbionts, but significantly more slowly than in NPC corals (p< 0.001) (39).…”
Section: Thermal Preconditioning Improves Bleaching Susceptibility Inmentioning
confidence: 93%
See 3 more Smart Citations